Social Construction of Masculine Women Identity - Fachrul Nurhadi, Zikri; Salamah, Ummu; Destari, Yully; Susanti Suseno, Novie (International Journal of Engineering and Technology, 2018)
The purpose of this study to discover and reveal the social construction of masculine woman identity in terms of externalization, objectivation, and internalization. This study used a qualitative approach, with a method or theory of social reality construction of constructivism paradigm. Data collection was done through in-depth interviews, participant observation, and literature. The study finding showed that the social construction of masculine woman identity in terms of externalization is influenced by internal and external factors. Internal factor is influenced by a family that makes informants show the social construction of masculine woman identity to the public. While external factor is influenced by association with male friend and technological advances (mass media) that have contributed to the formation of character, appearance style, and feeling to others. In general, social identity construction of masculine woman constructs her identity in a wayÂ showed that masculine woman does not always have a negative character. In this case, a masculine woman can survive and adapt to the family, campus and community environments. The research finding showed that appearance changes will only happen if there is a will from the masculine woman herself, and the comfort level of masculine appearance can not change the identity. Â Â